Análise da qualidade de vida no trabalho da indústria têxtil paulistana: estudo de caso múltiplo - Santana, Peri da Silva (2014)
The objective of this work wasanalyzing the Quality of Work Life (QWL) and address, the textile industry in the city of São Paulo, in São Paulo's textile industry, where with the processes of globalization in the economic system is developing as global factors become more important in policy and business practices, and in the textile industry, which loses strength, don t give a due attention in this regard. There is a redefinition of policies and practices in the production process and this is reflected in productivity with success factors for improving the quality of life of people in the workplace, being in textile production . It also focuses on the importance of Quality of Work Life (QWL), industry, knitting and textile manufacturing, where through a survey and see results through their concerns and influence the QWL in the production process and the role of management to see whether it has sustainability in the process, with improved performance and productivity. The overall objective of this study was to analyze the quality and productivity and job satisfaction in companies in the industry and textile industry. To achieve this goal, discussed the importance of quality, raising the profile and level of satisfaction of employees of companies identifying points of developing and publicizing actions that the company itself used as an action plan for improving the understanding of the environment work, according, where the conclusion was that companies are continually seeking increased productivity, where the results show that the concern for QWL in industries and impact on productivity and the business environment.